2008
DOI: 10.1021/la7032737
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Nanoscopic Water Layers on Hydrophobic and Hydrophilic Surfaces with Laser Light

Abstract: The evolutional function of ordered interfacial water near solid surfaces was postulated by Szent-Györgyi: "Life actually, may have started with building these water structures." Here we report their tunability with laser light on both hydrophobic and hydrophilic surfaces. On the former, the light caused their depletion--on the latter, an increase in fluidity--as measured by atomic force acoustic microscopy. Interfacial water layers play a key role in cellular recognition. Their tunability promises to revoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 15 publications
4
54
0
Order By: Relevance
“…Collectively these studies imply that so-called "non-bulk" water may "jacket" all biologically-active molecules and membranes, including intracellular organelles, mitochondria, DNA and RNA. This jacketing proposition is in principle consistent with a statement made by Tsai and Hamblin (2017), citing Sommer et al (2008), that "Cellular membranes are characterized by the presence of a thin (nanometer) layer of water that builds up on hydrophobic surfaces. "…”
Section: Introductionsupporting
confidence: 70%
“…Collectively these studies imply that so-called "non-bulk" water may "jacket" all biologically-active molecules and membranes, including intracellular organelles, mitochondria, DNA and RNA. This jacketing proposition is in principle consistent with a statement made by Tsai and Hamblin (2017), citing Sommer et al (2008), that "Cellular membranes are characterized by the presence of a thin (nanometer) layer of water that builds up on hydrophobic surfaces. "…”
Section: Introductionsupporting
confidence: 70%
“…14 The function of the intermittent irradiation mode is to facilitate the transport of the active compound into cells via transmembrane convection, a mechanism based on the interaction of 670-nm light with nanoscopic interfacial water layers on surfaces. 15,16 The cause of the convective flow across the plasma membrane is the simultaneous modulation of the density and viscosity of the nanoscopic interfacial water layers prevailing between intracellular surfaces (macromolecules and organelles). The effect is expected to be most pronounced in cells that are rich in mitochondria.…”
Section: 10mentioning
confidence: 99%
“…The surfaces employed by us to study interfacial water layers were hydrophobic or hydrophilic. [6][7][8][9] Normally, they preserved their original surface polarities during the period of the measurement, even in water containing nanoparticles. 8 Apparently, their presence had no effect on the prevalent interfacial water structure.…”
mentioning
confidence: 99%
“…Earlier we demonstrated that 670 nm laser light, applied in the same intensity range, depleted interfacial water layers in air, 6,7 and transformed their crystalline structure subaquatically. 8 From an analysis of the prevalent molecular situations at the relevant interfaces (loss of one degree of freedom due to unilateral restriction in mobility) we predicted interfacial water densities superior to that of bulk water.…”
mentioning
confidence: 99%
See 1 more Smart Citation